2021
DOI: 10.1186/s40337-021-00453-1
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods exploratory evaluation of burnout in frontline staff implementing dialectical behavior therapy on a pediatric eating disorders unit

Abstract: Background Eating disorders are life-threatening illnesses that commonly affect adolescents. The treatment of individuals with eating disorders can involve slow treatment progression and addressing comorbidities which can contribute to staff burnout. Dialectical behavior therapy (DBT) has emerged as a viable treatment option and has reduced staff burnout in several other settings. Our aim was to describe frontline staff burnout using mixed methodology on a DBT-trained combined inpatient/day hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…The evidence revealed that research involving CLS took place in hospitals and health centers (eg, inpatient hospital services), with 93 of the 105 studies conducted in this context representing 89% of the research (Figure 3). 7,12–14,17,19–21,33–117 Other contexts included ambulatory clinics (n = 4; 4%), 25,122–124 multicontext (n = 3; 3%), 23,120,121 community health (n=2; 2%), 24,118 dental office (n=1; 1%), 119 multi-context (n=3; 3%), 23,120,121 rehabilitation facility (n=1; 1%), 22 and proton treatment (n=1; 1%) 16 . These results suggest that the CLS’ workforce is most prevalent in hospitals and health centers.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The evidence revealed that research involving CLS took place in hospitals and health centers (eg, inpatient hospital services), with 93 of the 105 studies conducted in this context representing 89% of the research (Figure 3). 7,12–14,17,19–21,33–117 Other contexts included ambulatory clinics (n = 4; 4%), 25,122–124 multicontext (n = 3; 3%), 23,120,121 community health (n=2; 2%), 24,118 dental office (n=1; 1%), 119 multi-context (n=3; 3%), 23,120,121 rehabilitation facility (n=1; 1%), 22 and proton treatment (n=1; 1%) 16 . These results suggest that the CLS’ workforce is most prevalent in hospitals and health centers.…”
Section: Resultsmentioning
confidence: 95%
“…Research involving CLS was most prevalent in the USA (n = 84) representing 80% of the evidence 7,12–14,16,17,19–25,34,37–40,42,44,45,47–51,53–55,58–68,72,74–80,82,83,85–92,94–96,98,100–105,107–109,111–113,115–124 with research in Canada a distant second place (n=10) with 10% of the research 35,36,46,52,56,73,81,84,110,114 . The remainder of the evidence was from Australia, Europe, Mexico, and Taiwan with 1 to 2 articles from each country and 3 multicountry studies (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations